2008
DOI: 10.1172/jci32103
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of effector CD8+ T cells derived from central memory cells establishes persistent T cell memory in primates

Abstract: The adoptive transfer of antigen-specific T cells that have been expanded ex vivo is being actively pursued to treat infections and malignancy in humans. The T cell populations that are available for adoptive immunotherapy include both effector memory and central memory cells, and these differ in phenotype, function, and homing. The efficacy of adoptive immunotherapy requires that transferred T cells persist in vivo, but identifying T cells that can reproducibly survive in vivo after they have been numerically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
723
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 757 publications
(764 citation statements)
references
References 51 publications
37
723
2
2
Order By: Relevance
“…However, IFN-g-producing T cells are generally considered as differentiated and short-lived effector memory or effector T cells and do not correlate with long-term immunity as shown in a murine OVA-model [30]. Central memory T cells, which are typically characterized by IL-2 production [31], were shown in several infectious models, including CMV in primates [32] and in lymphocytic choriomeningitis virus (LCMV) in the murine system [33], to mediate long-term immunoprotection and to be associated with superior disease control as compared to effector memory T cells. Initially memory T cells were characterized based on the expression of the CC-chemokine receptor 7 (CCR7) as CCR7 -effector and CCR7 1 central memory T cells [31].…”
mentioning
confidence: 99%
“…However, IFN-g-producing T cells are generally considered as differentiated and short-lived effector memory or effector T cells and do not correlate with long-term immunity as shown in a murine OVA-model [30]. Central memory T cells, which are typically characterized by IL-2 production [31], were shown in several infectious models, including CMV in primates [32] and in lymphocytic choriomeningitis virus (LCMV) in the murine system [33], to mediate long-term immunoprotection and to be associated with superior disease control as compared to effector memory T cells. Initially memory T cells were characterized based on the expression of the CC-chemokine receptor 7 (CCR7) as CCR7 -effector and CCR7 1 central memory T cells [31].…”
mentioning
confidence: 99%
“…Stimulation of antigen-specific CD8 þ T cells using extensive cellular culture under specific antigenic stimulation does not induce a homogeneous cellular product but a high number of subpopulations with diverse differentiation status, different phenotypes and functional and migratory capacities. 16 Thus, Berger et al 17 showed that antigenspecific CD8 þ T E derived from a subset of memory T cells named effector memory (T EM ) survive for only a short period after adoptive transfer, and failed to home to lymph nodes or BM.…”
Section: Extensive Culture Changes the Differentiation Status Of Antimentioning
confidence: 99%
“…Therefore, selection of T CM cells would ensure that after adoptive transfer the cellular product consisting of T E cells would be able to persist durably in vivo and revert to the memory pool. 17,18 However, acquisition of terminal effector properties and an increase in cytotoxic activity in vitro generate less effective cells at triggering disease regression in vivo. 19 Thus, the more-differentiated cells, with superior in vitro antitumor properties, are less capable of mediating tumor regression upon adoptive transfer.…”
Section: Extensive Culture Changes the Differentiation Status Of Antimentioning
confidence: 99%
“…Several groups are currently exploiting gene transfer technologies to increase the life span and potential expansion of infused lymphocytes, 75 thus producing genetically modified tumor-specific T cells capable on one hand to target and eliminate tumor cells in vivo (effectors), and, on the other, to provide a continuous and persistent surveillance against the reappearance of tumor cells (central memory cells). This goal might be either achieved by expressing homeostatic cytokines, 76 or cognate receptors 77 into T lymphocytes, or by gene transfer and expansion of selected T-cell sub-populations with retroviral and lentiviral vectors.…”
Section: Graft-versus-host Disease S Mastaglio Et Almentioning
confidence: 99%